Microinfusion of Bupropion Inhibits Putative GABAergic Neuronal Activity of the Ventral Tegmental Area - Sanaz Amirabadi; Firouz Ghaderi Pakdel; Parviz Shahabi; Somayyeh Naderi; Mostafa Ashrafi Osalou; Ulker Cankurt (Basic and Clinical Neuroscience, 2014)
Introduction: The most common interpretation for the mechanisms of antidepression is the increase of the brain monoamine levels such as dopamine (DA). The increase of DA can reduce depression but it can also decrease the monoamine release because of autoreceptor inhibition. Although bupropion can decrease the dopamine release, there is evidence about stimulatory effects of chronic application of bupropion on ventral tegmental area (VTA) neurons. In this study, the intra-VTA acute microinfusion of bupropion on putative VTA non-Dopaminergic (VTA-nonDA) neuronal firing rates was evaluated by a single neuron recording technique.